Facile fabrication of porous Ti2Nb10O29 microspheres for high-rate lithium storage applications. (7th September 2017) - Liu, Guangyin; Jin, Bo; Bao, Keyan; Liu, Ying; Xie, Haiquan; Hu, Min; Zhang, Ruixue; Jiang, Qing
Abstract: Ti2 Nb10 O29 (TNO) microspheres are fabricated combining a solvothermal method with a subsequent heat-treatment. Structural and morphological properties of the as-prepared material have been characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and nitrogen adsorption/desorption. The electrochemical performance is evaluated by performing cyclic voltammograms and galvanostatic discharge/charge tests. The electrochemical characterization demonstrates that the as-prepared TNO microspheres exhibit a good electrochemical performance with a discharge capacity of 185 mAh g −1 after 200 cycles and a capacity retention of 94% at 10 C. Furthermore, since TNO may react with Li at a voltage above 1.0 V vs. Li + /Li, TNO microspheres could be the promising high-power anode materials for 2 V vs. Li + /Li lithium-ion batteries applications. Highlights: Ti2 Nb10 O29 (TNO) microspheres were prepared combining a solvothermal method with a subsequent heat-treatment. TNO microspheres used Ti(OC3 H7 )4 and NbCl5 as starting materials. TNO microspheres show excellent electrochemical properties at high current densities.